An integrative cultural branding and digital strategy model for strengthening regional tourism competitiveness - Iswara Sukma Windhyakirana; Bambang Jatmiko; Kholifah Fil Ardhi; Muhammad Zainal Abidin; Titi Laras; Sukardi Sukardi; Deny Ismanto (Jurnal Fokus Manajemen Bisnis, 2025)
This study analyzes the marketing strategy of Batik Sekarniti micro small medium entreprises through an integrated strengths-weakness-opportunity-threats and digital marketing approach to enhance tourism competitiveness in Kulonprogo, Yogyakarta, Indonesia. In the creative economy 5.0 era, micro small medium entreprises in the cultural sector must balance traditional craftsmanship with digital innovation to remain competitive. Batik Sekarniti symbolizes Kulonprogo’s cultural identity and has strong potential as a culture-based tourism icon. However, challenges such as limited marketing strategies, weak branding, and low digital marketing adoption hinder growth. This quantitative study surveyed 100 respondents. Data were analyzed using the structural equation modeling method to test relationships among variables. Results show that strengths-weakness-opportunity-threats  based marketing strategies have a significant positive effect on tourism competitiveness, and this relationship becomes stronger when mediated by digital marketing practices such as social media, e-commerce, and digital storytelling. The integration of strengths-weakness-opportunity-threats and digital marketing enables micro small medium entreprises to expand market reach, strengthen cultural narratives, and enhance regional branding. The implications of this study emphasize the necessity of continuous digital literacy development, collaborative branding programs between micro small medium entreprises and local governments, and policy support for creative economy ecosystems. Strengthening digital ecosystems and knowledge-sharing networks among batik entrepreneurs can foster innovation, sustainability, and inclusivity, positioning Kulonprogo as a competitive culture-driven tourism destination in the 5.0 era.